Plasma Diagnostics of Low Pressure Helium Glow Discharges at Different Working Voltages - Hanaa E. Jasim (Journal of Global Pharma Technology, 2020)
In addition to measurements of, the neutral gas temperature, the electron density and electron temperature plays a vital role in a low-pressure helium plasma characterization and processes. For instance, in biological and mass spectroscopy applications .In this paper, low pressure plasma of helium gas was generated between a flat planar anode and cathode electrodes. A cylindrical probe was constructed and employed to analyze plasma parameters of a structure discharging glow in a negative glow region. Electrons and ions currents of helium plasma have been measured at different discharges voltages and currents. Langmuir probe results at working pressure of 0.5 mbar indicate the electron temperature decreases and density increases as applied voltage increases which can be traced to the fact that electrons collide more frequently with plasma species. Keywords: Plasma diagnostics; Helium gas; Glow discharge; Langmuir probe.